2019
DOI: 10.1038/s41593-019-0342-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, biphasic CRF neuronal responses encode positive and negative valence

Abstract: SUMMARY Corticotropin-releasing factor (CRF) that is released from the paraventricular nucleus (PVN) of the hypothalamus is essential for mediating stress response by activating the hypothalamic-pituitary-adrenal (HPA) axis. CRF-releasing PVN neurons receive inputs from multiple brain regions that convey stressful events, but their neuronal dynamics on the timescale of behavior remain unknown. Here, our recordings of PVN CRF neuronal activity in freely behaving mice revealed that CRF neurons are act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
101
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 42 publications
10
101
2
Order By: Relevance
“…Despite the apparent neural activation resulting from acute LG treatment in slices, it is also possible that CRH cells were activated even prior to the recordings – by fasting itself, if it is a mild stressor (Kim et al . 2019); such effects could have been overlooked after slice isolation. We carefully tested this possibility in separate experiments, where activation of CRH neurons was estimated in vivo by c‐Fos protein expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the apparent neural activation resulting from acute LG treatment in slices, it is also possible that CRH cells were activated even prior to the recordings – by fasting itself, if it is a mild stressor (Kim et al . 2019); such effects could have been overlooked after slice isolation. We carefully tested this possibility in separate experiments, where activation of CRH neurons was estimated in vivo by c‐Fos protein expression.…”
Section: Resultsmentioning
confidence: 99%
“…An independent in vivo support came recently from Kim et al . (2019), who reported population Ca 2+ responses of CRH neurons both to stressors and appetitive stimuli, regulated at least in part by synaptic inputs to CRH cells. Remarkably, while GABAergic afferents to the PVN appear critical for metabolic responses (Cowley et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies indicated that the opposing valences of sensory stimuli are encoded by two separate populations of neurons, each of which represents either positive or negative valence of the stimuli 37,38 . By contrast, recent studies proposed an alternative strategy, wherein a single population of neurons responds to appetitive or aversive stimuli and represents the positive or negative valence of the stimuli by increasing or decreasing neuronal activity 39,40 . Specifically, CRF (corticotropin-releasing factor)-releasing neurons in the paraventricular nucleus of the hypothalamus are activated by aversive stimuli and inhibited by appetitive stimuli 40 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, recent studies proposed an alternative strategy, wherein a single population of neurons responds to appetitive or aversive stimuli and represents the positive or negative valence of the stimuli by increasing or decreasing neuronal activity 39,40 . Specifically, CRF (corticotropin-releasing factor)-releasing neurons in the paraventricular nucleus of the hypothalamus are activated by aversive stimuli and inhibited by appetitive stimuli 40 . Likewise, in C. elegans , experience-dependent modulation enables a single set of interneurons to elicit bidirectional responses to carbon dioxide, which can be either attractive or aversive, depending on prior experience 39 .…”
Section: Discussionmentioning
confidence: 99%